2023
DOI: 10.3390/pr11020590
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Antimicrobial Packaging for Extending the Shelf Life of Food

Abstract: Food packaging systems are continually impacted by the growing demand for minimally processed foods, changing eating habits, and food safety risks. Minimally processed foods are prone to the growth of harmful microbes, compromising quality and safety. As a result, the need for improved food shelf life and protection against foodborne diseases alongside consumer preference for minimally processed foods with no or lesser synthetic additives foster the development of innovative technologies such as antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(23 citation statements)
references
References 208 publications
0
23
0
Order By: Relevance
“…The alginate‐ and carrageenan‐based films are commonly produced by employing a solution casting approach, and it has been reported that the neat films are brittle, and physical properties (mechanical, barrier, and hydrophobicity) are relatively weak for food packaging purposes (Roy & Rhim, 2020d; Santos et al., 2022a; Wang et al., 2023). Therefore, to enhance the physical and functional performances of both films, usually plasticizers, other polymers, cross‐linkers, and bioactive functional ingredients (nanofillers, plant extract, bioactive compounds, natural colorant, and EOs) are usually added into the film‐forming formulation (Bose et al., 2023; Fadiji et al., 2023; Ghosh et al., 2023; Kishore et al., 2023; Roy, Ezati, et al., 2023; Roy, Zhang, et al., 2023). The combination of other polymers and the addition of plasticizers and cross‐linkers are highly effective to improve the packaging films’ physical properties; on the flip side, the incorporation of functional additives helps to impart the antioxidant, antimicrobial activity into the film (Khan, Priyadarshi, et al., 2023; Shankar & Rhim, 2018; Tran et al., 2020; Zhang et al., 2022).…”
Section: Alginate and Carrageenanmentioning
confidence: 99%
“…The alginate‐ and carrageenan‐based films are commonly produced by employing a solution casting approach, and it has been reported that the neat films are brittle, and physical properties (mechanical, barrier, and hydrophobicity) are relatively weak for food packaging purposes (Roy & Rhim, 2020d; Santos et al., 2022a; Wang et al., 2023). Therefore, to enhance the physical and functional performances of both films, usually plasticizers, other polymers, cross‐linkers, and bioactive functional ingredients (nanofillers, plant extract, bioactive compounds, natural colorant, and EOs) are usually added into the film‐forming formulation (Bose et al., 2023; Fadiji et al., 2023; Ghosh et al., 2023; Kishore et al., 2023; Roy, Ezati, et al., 2023; Roy, Zhang, et al., 2023). The combination of other polymers and the addition of plasticizers and cross‐linkers are highly effective to improve the packaging films’ physical properties; on the flip side, the incorporation of functional additives helps to impart the antioxidant, antimicrobial activity into the film (Khan, Priyadarshi, et al., 2023; Shankar & Rhim, 2018; Tran et al., 2020; Zhang et al., 2022).…”
Section: Alginate and Carrageenanmentioning
confidence: 99%
“…PEMA-based laminates can be used to improve the barrier properties of packaging materials, such as oxygen and moisture barriers, improving the shelf life of packaged products. [7,8] PEMA can be easily modified with other polymers or additives to enhance its properties further. For example, PEMA can be modified with impact modifiers to increase its toughness or with UV stabilizers to enhance its resistance to UV radiation.…”
Section: Recyclabilitymentioning
confidence: 99%
“…PEMA‐based laminates can be used to improve the barrier properties of packaging materials, such as oxygen and moisture barriers, improving the shelf life of packaged products. [ 7,8 ]…”
Section: Various Applications Of Polyethyl Methacrylate (Pema)mentioning
confidence: 99%
See 2 more Smart Citations